Formation of singularities of solutions to a 1D compressible radiation hydrodynamics model. (September 2022) - Li, Shengxin; Wang, Jing
Abstract: In this paper we are concerned with a 1D compressible radiation hydrodynamics model, which is described by a Navier–Stokes-elliptic coupled system of equations without viscosity. We prove that the smooth solutions to this model would blow up in finite time provided the first derivatives of the initial data are less than some negative constant although the initial data themselves are small. Moreover, it is shown that the singularity is indeed a shock singularity.